1985
DOI: 10.1111/j.1365-2559.1985.tb02827.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrolamellár hepatocellular carcinoma. An immunohistochemical and ultrastructural study

Abstract: Two cases of fibrolamellar carcinoma of the liver are reported in young female patients of 12 and 21 years of age. Small amounts of perinuclear alpha-fetoprotein were found, unrelated to hyaline globules, as well as alpha 1-antitrypsin in a periglobular fashion in isolated cells. Ferritin was present in a large number of cells. Ultrastructurally, the well differentiated nature of the neoplasm was substantiated by previously unreported findings such as intercellular lumina analogous to bile canaliculi and perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 19 publications
0
10
0
3
Order By: Relevance
“…Further studies in a larger number of fibrolamellar carcinomas will have to clarify whether a-HCG may have a marker function for this tumour. If this proves correct, it may be additional evidence that these tumours are biologically different from other types of hepatocellular carcinoma (Craig et al 1980, Caballero et al 1985, possibly being of neuroendocrine nature as has recently been suggested (Payne e f al, 1986).…”
Section: Discussionmentioning
confidence: 82%
“…Further studies in a larger number of fibrolamellar carcinomas will have to clarify whether a-HCG may have a marker function for this tumour. If this proves correct, it may be additional evidence that these tumours are biologically different from other types of hepatocellular carcinoma (Craig et al 1980, Caballero et al 1985, possibly being of neuroendocrine nature as has recently been suggested (Payne e f al, 1986).…”
Section: Discussionmentioning
confidence: 82%
“…29,30 Structures resembling neurosecretory granules have been noticed in some 29 but not all ultrastructural studies. 1,31 The significance of this 'neuroendocrine differentiation' remains unclear, but is unlikely to be helpful in distinction from conventional HCC as up to one-fourth of the latter may also show 'neuroendocrine differentiation'. 30,32,33 Immunohistochemistry for AFP was negative in all cases tested, similar to other studies, 8 although focal positive reaction in small groups of cells has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…30,32,33 Immunohistochemistry for AFP was negative in all cases tested, similar to other studies, 8 although focal positive reaction in small groups of cells has been reported. 31 Several studies have emphasized the better survival in fibrolamellar carcinoma compared to conventional hepatocellular carcinoma. 1,[3][4][5][8][9][10][11][12][13][14] However, these results could not be confirmed by many authors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the bile canaliculi, or the propensity of hepatocytes to polarize with canalicular lumina in vitro , may be retained in cells of HCC origin. Examples of this phenomenon come from histological data on human HCC, as well from the different hepatic cell lines that were mentioned in earlier sections of this review, such as WIFB and HepG2, and Can10 cells (60, 113, 200, 226, 357). Moreover, certain pathways that promote hepatic polarization may incidentally be upregulated in hepatic carcinogenesis.…”
Section: Hepatic Polarity In Diseasementioning
confidence: 99%